Answer:
Original function;
y = logbX
Transformation;
y = -5/3logb(x + 2) - 6
Explanation:
General form of a logarithmic function is given below;
y = logb X (log to base b)
Reflection over the y-axis
y value remains same, x becomes negative
y = - logb X
Vertical stretch by a factor of 5/3
This means that we multiply the whole function by 5/3
That will be;
y = -5/3logbX
Transformation right 2 units
This means that we add the value of 2 to the x-axis value
y = -5/3logb(x + 2)
transformation down 6 units
This means that we subtract 6 from the total y value
y = -5/3logb(x + 2) - 6